Response of the sea‐ice diatom Fragilariopsis cylindrus to simulated polar night darkness and return to light. (19th November 2019) - Morin, Philippe‐Israël; Lacour, Thomas; Grondin, Pierre‐Luc; Bruyant, Flavienne; Ferland, Joannie; Forget, Marie‐Hélène; Massicotte, Philippe; Donaher, Natalie; Campbell, Douglas A.; Lavaud, Johann; Babin, Marcel
Abstract: Arctic photoautotrophic communities must survive through polar night darkness until light returns in spring. We tracked changes in the cellular resource allocations and functional capacities of a polar sea‐ice diatom, Fragilariopsis cylindrus, to understand acclimation processes in both darkness and during the subsequent return to light. We measured parameters at specific time‐points over 3 months of darkness, and then over 6 d after a return to light. Measured parameters included cell number and size, cellular carbon and nitrogen quotas, lipid and pigment contents, concentration of key proteins of the photosynthetic system, photosynthetic parameters based on both variable fluorescence and carbon assimilation, and the level of nonphotochemical quenching. A stable functional state was reached within a few days after the transition to dark and was then maintained throughout 3 months of darkness. The dark period resulted in a decrease of lipid droplet cell quota (−6%), chlorophyll a cell quota (−41%) and the maximum carbon fixation rate per cell (−98%). Return to light after 1.5 months of darkness resulted in a strong induction of nonphotochemical quenching of excitation and a fast recovery of the maximum carbon fixation rate within 1 d, followed by a rapid increase in the cell number. Return to light after 3 months of darkness showed an increase of mortality or a profound downregulation induced over longer periods of darkness.